The strengths of biotech - Gretton, Linda Burak (Nature biotechnology, 2007)
The ability to identify and solve problems is a particularly critical skill for young companies whose processes and procedures are still in development. An individual who enjoys tackling obstacles and creating a clear path forward is someone who has a Restorative strength, according to the Gallup Organization. Gallup, known for its market research capabilities, has spent 25 years studying human psychology in over two million subjects in order to identify the strengths that are most prevalent within human society. Of the 34 dominant human strengths identified by Gallup, several seem to be held in common among the individuals who choose to apply to Targacept and who are ultimately hired. Although the company does not administer Gallup's Strengths Finder Profile to applicants, it does administer the assessment instrument to all new employees. Every one of Gallup's 34 dominant strengths is represented at Targacept, to a greater or lesser degree.